Efforts to Improve Mathematics Learning Outcomes Through the Application of the Problem Based Learning Model for Class VII F Students at SMP Negeri 9 Palu - Nurhalisa, Nurhalisa; Sukayasa, Sukayasa; Nurbaya, Siti (International Journal of Religion Education and Law, 2025)
The aim of this research is to improve the mathematics learning outcomes of class VII F students at SMP Negeri 9 Palu through the application of the Problem Based Learning (PBL) learning model in the mathematics subject of numbers. This research is class action research (Class Action Research) which consists of two cycles. Each cycle consists of action planning, action implementation, observation and reflection. The research subjects were students of class VII F at SMP Negeri 9 Palu. Data sources come from teachers and students obtained through observation, interviews, tests and document review. The data analysis technique used is descriptive analysis. The results of the research show that: (1) The teacher's ability to carry out learning using the Problem Based Learning (PBL) method to improve student learning outcomes in mathematics learning at SMP Negeri 9 Palu in cycle I had an average of 78% (sufficient), while in cycle II to 90% (very good), this shows an increase of 12%. (2) There was an increase in student learning outcomes in mathematics learning in Whole Numbers material using the Problem Based Learning (PBL) method in class VII-F of SMP Negeri 9 Palu, where student learning outcomes in cycle I had an average score of 69.70% with the percentage of completeness was 54.54%, while in the cycle II test results the average score was 71.81% with a percentage of completeness of 75.75%. This shows an increase in student learning outcomes by 2.11%.